ISYARAT SAINS DALAM HADITS NAHYI - Rizki Firmansyah (Al-Mubin, 2021)
Hadith is often also considered as "revelation" because it does not come from the passions of the prophet. So because he also comes from a transcendent substance, his values ​​also have similarities to those of the Quran even though the process of testing the authenticity of hadith has to go a long way. One of the values ​​it has is that it is loaded with scientific signs. There are many hadiths that command Muslims to do and stay away from something, but we often ask the reason behind it, with scientific explanations, the commands and prohibitions can be understood well. This study only discusses prohibitions related to food in terms of ways, sources, and places with certain hadiths. The method used in this research is qualitative with text analysis approach. The conclusions generated in this study are scientific factors from the prohibitions related to these hadiths for the health of the body for a long time